Chaotic Secure Communication : Principles and Technologies. - Sun, Kehui (De Gruyter, 2016)
The monograph begins with a systematic introduction of chaos and chaos synchronization, and then extends to the methodologies and technologies in secure communication system design and implementation. The author combines theoretical frameworks with empirical studies, making the book a pratical reference for both academics and industrial engineers.